Densification of Biomass and Waste Plastic Blends as a Solid Fuel: Hazards, Advantages, and Perspectives - Song, Bing; Hall, Peter (Frontiers in Energy Research, 2020)
This mini-review considers the densification of biomass blended with plastic wastes as an approach for waste management and sustainable fuel production from two perspectives; (1) We overviewed the pollutants generated during plastics combustion and their hazards. The control of these pollutants can be achieved as both reported in literature and by currently in-service municipal waste plants. (2) Advantages from densifying biomass/plastic blends as a solid fuel are indicated. Biomass/plastic briquettes or pellets are a potentially promising solid fuel with low costs, high volumetric heating values, high resistance to mechanical damage, and good durability performance under humid conditions. Moreover, the combustion of biomass/plastic blends with <10% plastics has no substantial negative effect on pollutants emission compared with that of biomass. Perspectives on densifying biomass/plastic blends as a solid fuel are proposed to realize the scale-up of this technique.